Enhancing the Phytoremediation of Heavy Metals by Combining Hyperaccumulator and Heavy Metal-Resistant Plant Growth-Promoting Bacteria - Zhang, Yong; Zhao, Shangjun; Liu, Sijia; Peng, Jing; Zhang, Hanchao; Zhao, Qiming; Zheng, Luqing; Chen, Yahua; Shen, Zhenguo; Xu, Xihui; Chen, Chen (Frontiers in Plant Science, 2022)
Heavy metals (HMs) have become a major environmental pollutant threatening ecosystems and human health. Although hyperaccumulators provide a viable alternative for the bioremediation of HMs, the potential of phytoremediation is often limited by the small biomass and slow growth rate of hyperaccumulators and HM toxicity to plants. Here, plant growth-promoting bacteria (PGPB)-assisted phytoremediation was used to enhance the phytoremediation of HM-contaminated soils. A PGPB with HM-tolerant (HMT-PGPB), Bacillus sp. PGP15 was isolated from the rhizosphere of a cadmium (Cd) hyperaccumulator, Solanum nigrum. Pot experiments demonstrated that inoculation with strain PGP15 could significantly increase the growth of S. nigrum. More importantly, strain PGP15 markedly improved Cd accumulation in S. nigrum while alleviating Cd-induced stress in S. nigrum. Specifically, PGP15 inoculation significantly decreased the contents of H2O2, MDA and O2•− in S. nigrum, while the activities (per gram plant fresh weight) of SOD, APX and CAT were significantly increased in the PGP15-inoculated plants compared with the control sample. These results suggested that the interactions between strain PGP15 and S. nigrum could overcome the limits of phytoremediation alone and highlighted the promising application potential of the PGPB-hyperaccumulator collaborative pattern in the bioremediation of HM-contaminated soils. Furthermore, the PGP15 genome was sequenced and compared with other strains to explore the mechanisms underlying plant growth promotion by HMT-PGPB. The results showed that core genes that define the fundamental metabolic capabilities of strain PGP15 might not be necessary for plant growth promotion. Meanwhile, PGP15-specific genes, including many transposable elements, played a crucial role in the adaptive evolution of HM resistance. Overall, our results improve the understanding of interactions between HMT-PGPB and plants and facilitate the application of HMT-PGPB in the phytoremediation of HM-contaminated soils.